isparitas Korban dan Pelaku Tindak Pidana Wanita dalam Pandangan Viktimologi dan Kriminologi - Joko Cahyono (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
Violent crimes against women identified in society today have increased significantly compared to previous years. In response to this phenomenon, both formal and substantive studies have been conducted by criminal law scholars in Indonesia in an effort to identify the underlying causes. Compared to earlier periods, crimes against women are now more easily detected. One prominent phenomenon is the advancement of technology, through which almost all abnormal or extraordinary activities are monitored, rapidly disseminated via social media and promptly responded to by law enforcement authorities. Several issues warrant further examination, particularly the criminal justice system’s orientation toward offenders, which has generated a sense of injustice in the provision of legal protection for victims of crime. This condition has resulted in victims—especially those of violent and sexual crimes—tending to remain silent, refraining from reporting incidents to law enforcement authorities, or, in other cases, refusing to act as witnesses in sexual violence cases. This phenomenon poses a significant obstacle to the effective operation of the criminal justice process and ultimately affects the success of comprehensive crime control efforts. Furthermore, the lack of comprehensive crime disclosure may lead to a sense of disparity in the administration of justice.